Clinical Recommendations From the European Society for Sexual Medicine Exploring Partner Expectations, Satisfaction in Male and Phalloplasty Cohorts, the Impact of Penile Length, Girth and Implant Type, Reservoir Placement, and the Influence of Comorbidities and Social Circumstances. (4th December 2019) - Osmonov, Daniar; Christopher, Andrew Nim; Blecher, Gideon A.; Falcone, Marco; Soave, Armin; Dahlem, Roland; Czeloth, Karen; Bannowsky, Andreas; Matanes, Emad; Ward, Sam; Martínez-Salamanca, Juan Ignacio; Bettocchi, Carlo; et al.
Abstract: Introduction: To date, several aspects of inflatable penile prosthesis (IPP) surgical procedure have been poorly studied. Aim: The aim of this study was to review the evidence associated with IPP implantation and provide clinical recommendations on behalf of the European Society for Sexual Medicine (ESSM). Overall, 130 peer-reviewed studies and systematic reviews, which were published from 2007−2018 in the English language, were included. Methods: MEDLINE and EMBASE were searched for randomized clinical trials, meta-analyses, and open-label prospective and retrospective studies. Main Outcome Measure: The panel provided statements exploring patients and partner expectations, satisfaction in male and phalloplasty cohorts, the impact of penile length, girth and implant type, reservoir placement, the influence of comorbidities, and social circumstances. Levels of evidence were provided according to the Oxford 2011 criteria and graded as for the Oxford Centre for Evidence-Based Medicine recommendations. Results: In the preoperative setting, it is fundamental to identify and interact with difficult patients with the intention of enhancing the surgeon's ability to establish the surgeon-patient relationship, reduce physical and legal risk, as well as enhancing patient satisfaction. To address this need, the mnemonic Compulsive, Unrealistic, Revision, Surgeon Shopping, Entitled, Denial, and Psychiatric ("CURSED") has been suggested to identify patients who are at high risk of dissatisfaction. The current recommendations suggest improving glycemic control in patients with diabetes. Available evidence suggests evaluating transplant recipients with the criteria of Barry, consisting of stable graft function for >6 months, avoidance of intra-abdominal reservoir placement, and low-dose immunosuppression. HIV status does not represent a contraindication for surgery. Smoking, peripheral vascular disease, and hypertension may be associated with an increased risk of revision surgery. Patients with spinal cord injury may receive IPP. Patients aged ≥70 years, as well as obese patients, can be offered IPP. The IPP implantation can be performed in patients with stable Peyronie's disease. Ectopic high submuscular reservoir placement can be considered as an alternative method. Clinical Implications: There is a relevant lack of high-level data and definite conclusions in certain areas remain difficult to draw. Strength & Limitations: All studies have been evaluated by a panel of experts providing recommendations for clinical practice. Because of lack of sufficient prospective data, some of the included studies are retrospective and this could be stated as a limitation. Conclusion: This ESSM position statement provides recommendations on optimization of patient outcome by patient selection, and individualized peri- and intra-operative management. ESSM encourages centers to collaborate and to create prospective, multicenter registries in order to address this topic of increasing importance.